(untitled) (Discussing Global Citizenship through Collaborative Online International Learning (COIL) - Virtual Exchange (VE) in Language Learning and Teaching: Symposium Proceedings, 2023)
Virtual exchange (VE) between different English language teaching (ELT) contexts can afford opportunities to develop intercultural communicative competence (ICC) while also offering a window to reflect on different realities in terms of ELT. To this end, two ELT programmes integrated a VE project into their syllabi to provide pre-service teachers with opportunities to experience VE with reflection and development of ICC. The present account aims to describe and reflect on the GAZUFES (Gazi University and UFES University) VE project that involved pre-service teachers, tutors, and teacher trainers in a university in Brazil and another in Türkiye. GAZUFES was in turn part of the large-scale Erasmus+ KA3 Policy Experimentation European Virtual Innovation and Support Networks for Teachers (VALIANT) project. The exchange had some positive outcomes, but the sudden return to in-person classes at the end of the pandemic in the Brazilian university negatively affected the integration of GAZUFES into the Brazilian curriculum and the number of participants from Brazil. Despite the unequal number of students involved in the project, those who participated were very motivated and engaged in reflective and stimulating interactions.